Business model reinvention: Impacts of Covid-19 on the fitness gym industry - Huguet, Léa Camille Tiphaine (2022)
Fitness gyms are experiencing a particular turmoil due to the Covid-19 crisis. The fitness industry is at the heart of wellness and health and is one of the most affected by the pandemic since 2020 (Baron, 2021). The closure of gyms, the cancellation of memberships, and the advent of free online fitness classes are undeniable challenges to face. Fitness gyms must adapt quickly and understand the new needs of their customers. To this extent, fitness gyms need to rethink their business models to overcome this Covid-19 crisis. This research aims to understand the major impacts of Covid-19 on the fitness gyms industry, identify the main changes is and present a possible reinvention of a business model to guide fitness gyms in a post-pandemic era. A literature review has been completed, a survey conducted on social medias and in-depth interviews conducted with diverse fitness gyms professionals exclusively in France. The key findings that can be retained are that fitness gyms should now offer more flexibility, accessibility, and security to their members.